5, 5′-Dibenzoimidazole as building block for a new 3D Co(II) coordination polymer: A combined EPR and DFT study using UB3LYP model. (1st October 2019) - Datta, Amitabha; Massera, Chiara; Garribba, Eugenio; Frontera, Antonio
Graphical abstract: A new Co(II) three dimensional polymer is afforded; the topological overview and EPR interpretation was discussed. Additionally, the DFT computation study was explored applying the UB3LYP/def2-TZVP level of theory. Abstract: A new Co(II) three-dimensional coordination polymer, [Co(L)(L′)] n (1 ) [where L = 5, 5′-dibenzoimidazole, and L′ = doubly deprotonated terephthalic acid] has been synthesized hydro(solvo)thermally and its molecular and crystal structure have been elucidated through single crystal X-ray diffraction analysis. Each Co(II) ion displays a slightly distorted trigonal bipyramidal geometry, the apical positions being occupied by the nitrogen atoms of two symmetry-related dibenzoimidazole ligands, while the oxygen atoms from three distinct terephthalic acids are in the equatorial plane. Considering the Co2 C2 O6 dimeric moieties as nodes, and the ancillary ligands as connectors, the structure can be simplified as a 8-c uninodal net of the typebcu, body centered cubic, with point symbol 4 24 ·6 4 and vertex symbol [4·4·4·4·4·4·4·4·4·4·4·4·4(3)·4(3)·4(3)·4(3)·4(3)·4(3)·4(3)·4(3)·4(3)·4(3)·4(3)·4(3)·*·*·*·*]. The EPR spectra for1 have been reported, showing g || = 2.176 and g ⊥ = 2.052 at RT (room temperature), and g || = 2.172 and g ⊥ = 2.060 at LNT (liquid nitrogen temperature). Finally, the electronic nature of the molecular geometry of1 has been explored by DFT computation applying the UB3LYP/def2-TZVP level of theory, showing the energy difference between the high spin and low spin configurations.